S-Carpool: The Apps Development For UniKL MIIT Students - Hasbullah, Siti Salwa; Sallehhuddin, Nur Asyiqin (Journal of Computing Technologies and Creative Content, 2017)
Recently, the students studies in the capital of city such as UniKL MIIT students having more difficulty regarding on getting nearby public transportation within their campus. This is due to the cost of public transportation is increased and it will able to burden the students daily life. It is also probably makes the students face the issues of insufficient and hard to find the vehicle or transportation that can have the similar direction within the UniKL MIIT Campus. The aim of this project is to develop S-Carpool Mobile Application system for UniKL MIIT students that provide students the easiest and fastest way to move from one place to another place. This application will help students to use their mobile applications in order to book a ride from UniKL MIIT to the any nearby destination requested. The use of mobile application nowadays give a various opportunity especially to the students to fully utilized the easiest and fastest way to help them move from one destination to another destination. By using this S-Carpool: The Apps Development For UniKL MIIT Students, also can help students to find trustable and comfortable friends for car ride to avoid unwanted situation especially for the safety purpose. Besides, this project also will be able to help them to save cost by sharing the payment for every car ride. The use of Rapid Application Development (RAD) methodology model is developed to meet with the objective of this project. The outcome of this S-Carpool: The Apps Development For UniKL MIIT Students, the development system will not provide the benefit directly to the students as a whole but also for the driver which is also the students from UniKL MIIT to generate extra income to support their students’ life that very challenging nowadays. This project also will be able to expand the use of the mobile application not only to the students but also to the staff and people who works in UniKL as a whole.  As a conclusion, the proposed S-Carpool: The Apps Development For UniKL MIIT Students will benefits user in terms of time saving, early exposure and proposed new transportation method to help students easy to move from one destination to other destination.